Preliminary Study of Yttrium Extraction from Tin Slag Using Hydrochloric Acid - Rachmat Fauzi Hidayat; Kurnia Trinopiawan; Mohammad Zaki Mubarok; Rommy Rommy; Riesna Prassanti; Aditya Widian Putra; Amalia Ekaputri Hidayat; Kurnia Setiawan Widana; Tri Purwanti; Roza Indra Laksmana; Triyono Basuki; Afiq Azfar Pratama; Suci Indryati (EKSPLORIUM, 2025)
Tin slag, a byproduct of tin smelting, comprises several important metals, including yttrium, tantalum, manganese, iron, aluminum, titanium, and others. As an element that is used a lot in advanced materials, the separation of Yttrium becomes one of the most important steps in rare earth elements extraction. By using the alkali fusion process and leaching method, yttrium in the tin slag has been successfully extracted. The tin slag was subjected to an alkali fusion treatment with sodium hydroxide at a temperature of 700 °C, and the frit was ground into several particle sizes of +100 to -325 mesh using a laboratory ball mill and mortar. The frit was then leached using hydrochloric acid, with four parameters used: temperature, acid concentration, particle size, and stirring speed. The extracted yttrium reached a percentage of up to 86.94% at a temperature of 80 °C, acid concentration of 2 M, particle size of -325 mesh, and stirring speed of 150 rpm.